2017
DOI: 10.1021/acs.jmedchem.7b01083
|View full text |Cite
|
Sign up to set email alerts
|

Application of the Ugi Multicomponent Reaction in the Synthesis of Reactivators of Nerve Agent Inhibited Acetylcholinesterase

Abstract: Recently, a new class of reactivators of chemical warfare agent inhibited acetylcholinesterase (AChE) with promising in vitro potential was developed by the covalent linkage of an oxime nucleophile and a peripheral site ligand. However, the complexity of these molecular structures thwarts their accessibility. We report the compatibility of various oxime-based compounds with the use of the Ugi multicomponent reaction in which four readily accessible building blocks are mixed together to form a product that link… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 18 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…Novelo xime structures synthesized using the Ugi multicomponent reaction. [96] Chem.E ur.J. 2019, 25,5337 -5371 www.chemeurj.org tion of the cyclosarin-and tabun-inhibited hAChE;h owever, the pyridinium and imidazole oximes, in additiont ot he hydroxyiminoacetamides, were able to reactivate sarin-inhibited AChE.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
See 2 more Smart Citations
“…Novelo xime structures synthesized using the Ugi multicomponent reaction. [96] Chem.E ur.J. 2019, 25,5337 -5371 www.chemeurj.org tion of the cyclosarin-and tabun-inhibited hAChE;h owever, the pyridinium and imidazole oximes, in additiont ot he hydroxyiminoacetamides, were able to reactivate sarin-inhibited AChE.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
“…The work of de Bruijn et al made use of am ulticomponent reaction, the Ugi reaction, to generate as mall diverse library of both charged and uncharged oxime reactivators of OP-inhibited AChE ( Figure 11). [96] The Ugi multicomponent reactioni sa condensation reaction that combinesa na ldehydeo rk etone, carboxylic acid, amine, and an isocyanide in as ingle reaction. Such ah ighly efficient reactiont hen allows the synthesis of a diversel ibrary of compounds rapidlya nd easily,a sw as exploited by de Bruijn et al In their work, the carboxylic acid moiety was attached to various oximes and possessed variousl inker lengths.…”
Section: Recent Results From Efforts To Develop Broad Scope Reactivatmentioning
confidence: 99%
See 1 more Smart Citation
“…Apart from these interactions, (R)-Boc-nipecotic acid might also introduce as a carboxylic acid moiety source, which can be attached to various oximes that have been successfully proven as a potential antidote. A study carried out by de Koning et al (2017), which reported the…”
Section: Docking Study Of the Selected Compounds Towards Sarin-inhibited Hachementioning
confidence: 99%
“…Multicomponent reaction (MCR) has advantages of atom economy, high efficiency, and fast building structural diversity and complexity of compound libraries and becomes a powerful tool in drug synthesis and discovery. ,, Considering that heterocycles have diverse bioactivities, we are interested in their MCR synthesis and bioactivities . Pyrrolidone rings are important heterocycles with a wide range of pharmacological activities, such as G0/G1-phase arresting agents VI .…”
Section: Introductionmentioning
confidence: 99%